A colorimetric assay with leuco crystal violet for the detection of inorganic phosphate in water - Ahmed, Minhaz Uddin; Arshad, Fareeha (Vietnam Journal of Science and Technology, 2023)
Phosphate enters the aquatic system through runoff from pastures, croplands, urban areas, and sewage treatment systems and fosters algal bloom causing eutrophication at higher concentrations in water. Therefore, controlling its concentration through routine monitoring of water quality in aquatic ecosystems is essential. Using a smartphone camera and colour analysis app, a simple colourimetric technique was developed to quantitatively detect inorganic phosphate in natural and treated drinking water samples using colourless leuco crystal violet (LCV). Upon reaction with phosphate (PO43−), LCV forms leuco crystal violet phosphate (LCV-P) complex with a violet colour and shows maximum absorbance at 583 nm. A light-sensitive colourimetric box with in-built LED light was constructed to maintain the consistency of the image quality for precise and accurate measurement. The Red, Green and Blue (RGB) analyses of the digital images were done to determine the linear response of the intensity of G against the concentration of the LCV-P complex. A microplate reader was also used to analyse the UV-Vis absorbance of the samples to validate the results further. Under optimum conditions, the colourimetric assay achieved a detection limit of 0.25 μM with a linear range between 0.1 and 1 μM. Thus, the proposed colourimetric assay was highly sensitive and selective towards phosphate in natural and drinking water samples.